(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to examine the extent of the application of Activity-Based Budgeting (ABB) in banks and its impact on the financial performance of commercial banks in Libya. The study adopted a descriptive-analytical approach, where a questionnaire was developed and distributed to a sample of employees in commercial banks. The study population consisted of department heads and managers directly related to the subject within commercial banks in the city of Sorman. A random sample of (40) individuals was selected, of which (29) valid questionnaires were returned for analysis, indicating a response rate of (73%), with some loss in distributed forms. The data were analyzed using the Statistical Package for the Social Sciences (SPSS). The study concluded that there is a deficiency in the application of Activity-Based Budgeting (ABB), reflected in the lack of flexibility in the organizational structure of banks to accommodate necessary adjustments during budget implementation. Additionally, senior management was found to be insufficiently supportive in facilitating the implementation of budgeting systems, and most accounting staff lacked adequate knowledge and awareness of ABB. The study proposed several recommendations, including restructuring banks’ organizational frameworks to enhance flexibility in implementing budgets, conducting training programs and workshops to improve awareness and understanding of ABB, and providing both financial and moral support from top management to ensure effective application of Activity-Based Budgeting.